Implementasi Manajemen Kurikulum Merdeka di SD Perguruan Buddhi Tangerang - Afifah, Najwa; Huliatunisa, Yayah (YASIN, 2023)
Education, in its process, requires the implementation of curriculum management, so that planning, implementation, and evaluation can run effectively, efficiently and optimally as an effort to empower various learning resources, learning experiences, and curriculum components. In its journey, the curriculum continues to experience various dynamic changes which are interpreted as improvements. The purpose of this study is to comprehensively describe curriculum management at SD Perguruan Buddhi Tangerang, qualitatively descriptive, through interviews with school principals, observations, and documentation studies. The results showed that the process of improving this learning system was very quickly responded to by the Buddhi College Elementary School, with the use of the independent curriculum which had entered the second stage, namely independence change. This is as a result of the readiness of all school management to accept changes both from the principal, teacher readiness, and school facilities. Although it is undeniable that the implementation process still faces obstacles, school management always tries to be ready to face these changes.